The Quest for Gender-Sensitive and Inclusive Transport Policies in Growing Asian Cities - Thynell, Marie (Social Inclusion, 2016)
In cities all over the world, growing numbers of women are working or studying further away from home than ever before. This article presents policies by the World Bank and recommendations by the United Nations to improve conditions for women’s mobility in cities. Although these stress different factors affecting women’s experiences of traffic and transport, they all agree about the importance of enabling women’s mobility. However, gender-sensitive policies have been largely unsuccessful. This article presents examples of conditions for women in New Delhi and other rapidly growing Asian cities that illustrate how gender norms operate. This study uses the perspectives of development research and gender studies to examine economic and political initiatives and the way women act and interact with transport in local contexts. It facilitates critical reflection upon existing transport policies and suggests ‘how’ women’s needs may be effectively addressed. More in-depth knowledge about women’s needs and the problems they face when travelling will be useful for designing of policies that address more than simply the harassments of women. More inclusive urban access would enhance conditions for women and enable them to make choices according to their needs. In this way, social science and policy will cross-pollinate one another.